Experience of Chilean curricular innovation of the Law career of the University Academy of Christian Humanism - Martínez Montenegro, Isnel (Revista Pedagogía Universitaria y Didáctica del Derecho, 2022)
In this research, a qualitative study is developed on the process of the evaluation of curricular innovation carried out in the study plan of the year 2017 of the Law career of the Academia de Humanismo Cristiano University. This article aims to analyze the constructive process of the evaluation carried out by the career as a result of the commitments assumed with the innovation that began through the Curricular Appropriation Program of the University. During its implementation, the instruments and institutional guidelines were designed and adjusted for the application of this evaluation to the different actors of the community of the Law career and a documentary analysis of the course programs, the coverage tables, the matrices was carried out. of taxation, the curriculum and forms that were applied to students, teachers, employers and experts. Among the results is the identification of strengths and weaknesses and the proposal of necessary modifications to improve the study plan and the graduation profile, in such a way that they are coherent and respond to the current challenges and in which must develop.